DETERMINAN HIPERTENSI DI KABUPATEN MINAHASA SULAWESI UTARA - Marini Podayow; Jeini Ester Nelwan; Eva Marianne Mantjoro; Wulan Pingkan Julia Kaunang; Ardiansa A.T. Tucunan (Bahasa Indonesia, 2023)
Hypertension or what is often called high blood pressure usually occurs at systolic blood pressure ≥140mmHg and diastolic blood pressure ≥90mmHg. Hypertension has several factors that can trigger (determinant) the occurrence of hypertension, including the risk factors of age, gender and nutritional status. This study aims to determine the determinants of hypertension in Minahasa District, North Sulawesi Province. This is an observational study with a cross-sectional approach. The sample used was 110 respondents. The sampling method is simple random method. The variables studied were the incidence of hypertension, age, gender and nutritional status. This study used form sheets, tensimeters, height meters, weight scales, and computers. The statistical test used was the chi square test with a significance level of 95% (α = 0.05). The results showed that there was a correlation between age and hypertension (p-value = 0.002), and there was no correlation between gender and hypertension (p-value = 0.819) and there was a correlation between nutritional status and hypertension (p value = 0.003). It can be concluded that age and nutritional status were determinants of the incidence of hypertension in Minahasa Regency.